La tercera década del siglo XXI: nuevos desafíos teóricos y epistemológicos para las relaciones internacionales. - SÁNCHEZ MUGICA, ALFONSO (CONfines de Relaciones Internacionales y Ciencia Política)
International Relations is a science that currently enjoys great dynamism in many parts of the world, largely due to different political and social changes typical of the early years of a new decade, in this case, the third decade of the 21st century. However, it faces challenges of a disciplinary nature, especially regarding its theoretical and methodological frameworks and structures. The loss of the Anglo-Saxon centrality is now accompanied by the appearance of new theoretical paradigms, a strong post-positivism, and first-hand epistemological elements that require the opening of a broader and more plural dialogue among specialists from all over the world. Some components of this debate should address non-Western contributions, the question of how globalization is understood as well as new interdisciplinary approaches such as those concerning the paradigm of complexity.